An outbreak of serotype 19A pneumococcal pneumonia in a relief facility in Japan. (30th December 2022) - Nagano, Kei; Kawasaki, Satoshi; Moro, Hiroshi; Chang, Bin; Bamba, Yuuki; Yamamoto, Ayako; Morita, Masatomo; Ohnishi, Makoto; Shibata, Satoshi; Koizumi, Takeshi; Aoki, Nobumasa; Honma, Yasuo; et al.
Abstract: An outbreak of serotype 19A Streptococcus pneumoniae occurred among the residents of a relief facility. Pneumonia developed in 5 of 99 residents (attack rate, 5.1%). We obtained pharyngeal specimens from non-onset residents, and S. pneumoniae was isolated from 6 individuals (6.4%), 5 of whom had serotype 19A.